2002
DOI: 10.1037/0022-006x.70.2.444
|View full text |Cite
|
Sign up to set email alerts
|

Sudden gains in recovering from depression: Are they also found in psychotherapies other than cognitive-behavioral therapy?

Abstract: Following T. Z. Tang and R. J. DeRubeis's (1999) report of sudden gains (a sudden and substantial improvement in depression symptoms in one between-session interval) in cognitive-behavioral therapy (CBT) for depression, this study explored sudden gains in supportive-expressive (SE) psychotherapy. Studies suggested that CBT sudden gains are caused by cognitive changes, which is a factor specific to CBT. Thus, sudden gains might not be expected in SE psychotherapy. Contrary to that expectation, sudden gains in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
126
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(144 citation statements)
references
References 9 publications
15
126
2
1
Order By: Relevance
“…In contrast, we observed no differences in outcome between individuals with and without sudden gains at the posttreatment or 6-month follow-up assessments. This finding is in line with some studies (Tang et al, 2002;Vittengl et al, 2005) but at odds with other reports (Gaynor et al, 2003;Hardy et al, 2005).It is interesting that we found that participants with sudden gains had higher levels of pretreatment social anxiety. Similarly, previous studies on sudden gains during the treatment for depression also observed higher levels of pretreatment symptomatology in individuals who later experienced sudden gains (e.g., Vittengl et al, 2005).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, we observed no differences in outcome between individuals with and without sudden gains at the posttreatment or 6-month follow-up assessments. This finding is in line with some studies (Tang et al, 2002;Vittengl et al, 2005) but at odds with other reports (Gaynor et al, 2003;Hardy et al, 2005).It is interesting that we found that participants with sudden gains had higher levels of pretreatment social anxiety. Similarly, previous studies on sudden gains during the treatment for depression also observed higher levels of pretreatment symptomatology in individuals who later experienced sudden gains (e.g., Vittengl et al, 2005).…”
supporting
confidence: 91%
“…Predictions for long-term maintenance of gains, however, were mixed. Some studies showed better outcomes at follow-up for patients with sudden gains (Gaynor et al, 2003;Hardy et al, 2005;Stiles et al, 2003;Tang & DeRubeis, 1999b), whereas other studies found no differences at follow-up for patients with and without sudden gains (Tang et al, 2002;Vittengl et al, 2005). Vittengl et al (2005) reported that patients with sudden gains during acute treatment actually showed more depressive symptoms and negative failure attributions at follow-up than those who had not experienced sudden gains.…”
mentioning
confidence: 99%
“…However, others have had difficulty replicating this finding using alternate assessment methods in a CBT-oriented intervention (Kelly, Roberts & Ciesla, 2005). Further, as previously stated, sudden gains have been found to occur across several treatment modalities (Tang & DeRubeis, 1999b;Tang et al, 2002Tang et al, , 2005Stiles et al, 2005;Andrusyna et al, 2006) and among samples who are not receiving active treatment (Kelly et al, 2007;Vittengl et al 2003). This suggests that the precipitants and meaning of sudden gains in the remediation of depressive symptoms have yet to be fully understood.…”
Section: Introductionmentioning
confidence: 77%
“…It is especially interesting to note that in previous work, Tang and colleagues (Tang, Luborsky & Andrusyna, 2002) found that sudden gains occurring during the course of supportiveexpressive (SE) therapy, a derivative of psychodynamic therapy that is arguably closer in nature to IPT than is CBT, were less robust and did not predict longer term outcomes as did CBT related sudden gains. These authors suggest that SE therapy-related sudden gains are less robust due to the relative complexity of SE compared to CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Formulation of new bio-insecticides, particularly those based on Neem tree extract, was an exciting option for integrated pest management programs in Kakira. Tang et al (2002) accept that plant-derived insecticides have various benefits, including selectivity, greater safety for non-target organisms, and compatibility with biological control organisms. Since aphids have built resistance against chemical pesticides; alternative options have to be thought of to ensure controlled aphid pest populations.…”
Section: Introductionmentioning
confidence: 99%